Pengaruh Model Pembelajaran Berbasis Proyek (Pjbl) Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ips Kelas V Sd Inpres 3 Tondo - Rinawanti Rinawanti; Nurul Fitria Aras; Rizal Rizal; Ryan Andhika Pratama (JURNAL DIKDAS, 2024)
This study aims to determine the effect of project-based learning model (PjBL) on the learning motivation of fifth grade students at SD Inpres 3 Tondo. The research method used was a quasi experiment type nonequivalent control group design. In this study, the VA and VB classes of SD Inpres 3 Tondo. The research instruments were learning motivation questionnaire, PjBL questionnaire, teacher and student observation sheets. The data analysis technique in this study is a hypothesis test using a non-parametric statistical test using the Man Whitney U test technique and based on the posttest calculation of the control and experimental classes obtained Asymp. Sig. (2-tailed) of 0.046 <0.05. This shows that Ho is rejected and Ha is accepted, so the average social studies learning motivation of students in the experimental class is different from the average social studies learning motivation of students in the control class and it can be concluded that there is an effect of using a project-based learning model on social studies learning motivation of fifth grade students of SD Inpres 3 Tondo.